Detection of Human Papillomavirus Using Hybrid Capture 2 in Oral Brushings From Patients With Oropharyngeal Squamous Cell Carcinoma. Issue 5 (August 2015) - Jarboe, Elke A.; Willis, Mark; Bentz, Brandon; Buchmann, Luke; Hunt, Jason; Ellis, Gary; Layfield, Lester
Abstract : Detection of high-risk (HR) human papillomavirus (HPV) in oropharyngeal squamous cell carcinoma (SCC) has important prognostic implications; patients exhibit improved survival compared with patients with HPV– SCC. Oral brushing and rinsing samples were obtained from patients with oropharyngeal, oral cavity, or hypopharyngeal SCC and tested for HR-HPV using Hybrid Capture 2 (HC2; QIAGEN, Valencia, CA). HR-HPV in situ hybridization (ISH) was performed on biopsy tissue samples from the same patients. Oral cytologic samples from 16 SCCs were tested by HC2. Biopsy tissue samples were available for ISH in 11 cases. Five oropharyngeal SCCs were HR-HPV+ by ISH and HC2 (oral brushing). Of the oropharyngeal SCCs, 2 were positive by HC2 (oral brushing) and negative or equivocal by ISH. We found that 2 oral cavity carcinomas and 2 hypopharyngeal carcinomas were negative by HC2. One hypopharyngeal cancer was positive by ISH. All oral rinsing samples were negative by HC2. HC2 may be an effective method of determining HR-HPV status in patients with oropharyngeal SCC.